The Effect of CEO Characteristics on Water Disclosure: The Moderating Role of Independent Commissioners in Companies Listed in the Indonesian Stock Exchange - Ivone, Ivone; Ramadana, Mariska; Syafitri, Icha (Jurnal Samudra Ekonomi dan Bisnis, 2026)
This study analyzes the influence of Chief Executive Officer (CEO) characteristics and corporate governance mechanisms on the level of water disclosure in public companies in Indonesia following the implementation of the 2021 edition of the Global Reporting Initiative (GRI) 303. Independent variables include CEO age and CEO-Founder status, with independent commissioners as a moderating variable. Control variables include company age, company size, return on assets, leverage, and Big-4 auditors. Data were obtained from non-financial companies listed on the Indonesia Stock Exchange for the 2021–2023 period, with a total of 647 annual observations. The analysis used panel data regression with cluster robust standard errors. The results show that CEO age and CEO-Founder have a significant negative effect on water disclosure, while the interaction between CEO-Founder and independent commissioners has a significant positive effect. These findings confirm that corporate governance and performance play a greater role in driving water disclosure than CEO demographic factors.